Stress Intensity Factor Solutions for CTS Mixed Mode Specimen (Fracture and Structural Integrity, 2019)
The Compact Tension Shear (CTS) specimen is used to study fracture and fatigue under mixed mode I/II loading conditions. Existing K solution was developed for fracture studies and it does not consider the effect of crack deflection. The aim of present work is to develop KI and KII empirical solutions for cracks with different crack length, loading angle and crack orientation. A total number of 1120 cracked geometries were studied numerically by the finite element method and solutions were fitted to numerical predictions. An average difference of 0.53 % was found between numerical predictions and the solution proposed for KI. For KII the difference is higher, but the equivalent stress intensity factor showed a difference of only  1% because KII is lower than KI. Experimental work was developed to study fatigue crack growth in CTS specimens. The cracks always adopted a direction approximately normal to loading direction, i.e., tend to propagate under mode I.
Keywords: CTS specimen; Stress intensity factor solution; Mixed mode